Association Between Smoking and Suicidal Behaviors Among Adolescents in the Republic of Korea. Issue 4 (October 2015) - Park, Sunhee; Kim, Junghee
Abstract : Abstract: Smoking and suicidal behaviors are significant health problems in adolescence. To address these two important health problems in youth, it is critical to understand the associations between them. Thus, this study aimed to explore the relationships between smoking and suicidal behaviors in adolescence. This study analyzed secondary data obtained from a national survey of Korean adolescents (i.e., the 7th Korea Youth Risk Behavior Web-Based Survey). Respondents were divided into two samples (38, 474 middle school students and 37, 169 high school students). In each sample, sample characteristics, smoking behaviors, and suicidal behaviors were examined using descriptive statistics (means and frequencies). The associations between smoking and suicidal behaviors were investigated using multivariate logistic regression analyses. To obtain more accurate findings, the complex sampling design employed in the national survey was incorporated in the analyses. Lifetime smokers and daily smokers made up 20% and 13% of the middle school sample and 32% and 29% of the high school sample, respectively. In both samples, of the three suicidal behaviors, the proportion of suicidal ideation was the greatest (20%), followed by suicide plans (6%–8%) and suicide attempts (4%–5%). This study revealed statistically significant associations between smoking and suicidal behaviors. Furthermore, most analyses revealed noncausal dose-related associations between these behaviors. On the basis of the study findings, health professionals should implement concurrent strategies targeting both smoking and suicidal behaviors rather than focus on them separately to address related health problems.